ANALISIS PENDAPATAN DAN SALURAN PEMASARAN BERAS ARUK - Eni Karsiningsih; Henny Helmi; Muhammad Soleh Rafsanjani (Journal of Integrated Agribusiness, 2021)
Aruk rice is one of the typical foods of local cultural heritage from the Province of the Bangka Belitung Islands that must be preserved and preserved. Aruk rice is also widely consumed by people with diabetes because it serves as a source of carbohydrates that are safe for the body. This study aims to determine the process of making aruk rice carried out by Kelompok Wanita Tani (KWT) Maju, to determine the income level of the group and members of KWT Maju from selling aruk rice, and to determine the marketing channel of aruk rice carried out by KWT Maju. The research method used is the case study method. The sampling technique was carried out by census, by making all members of Kelompok Wanita Tani Maju as respondents. The results showed that the processing of cassava into aruk rice carried out by Kelompok Wanita Tani Maju in Kemuja Village was still manual with simple equipment and required a relatively long time of 7-10 days. KWT Maju's income from making aruk rice is Rp. 1,299,475.02 per month. This income will be divided in two, namely 15% for group cash and 85% divided for group members. Meanwhile, the average income of each group member is Rp. 69,034.61 per month. There are 2 marketing channels for aruk rice, namely 1) marketing of aruk rice from KWT Maju directly to consumers and 2) marketing of aruk rice from KWT Maju -> Retailers (pharmacies) -> consumers.